2003
DOI: 10.1080/09593330309385652
|View full text |Cite
|
Sign up to set email alerts
|

Microbial and copper adsorption by smectitic clay‐an experimental study

Abstract: The objective of this study was to quantify copper-, bacteria- and bacteriophage-binding capacities of natural clay with the aim of predicting the adsorption of heavy metals, human pathogenic bacteria and viruses by a clayey landfill liner. X-ray diffraction analysis of six natural clays showed that the dominant phase in all deposits consists of smectites together with illite, kaolin and, sometimes, palygorskite and sepiolite. The specific surface areas of different clay substrates were very high ranging from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 21 publications
0
11
0
1
Order By: Relevance
“…They can firmly and selectively bind harmful substances from feeds in the intestines and thus reduce their absorption across the intestinal mucosa and resulting toxic effect (Knezevic and Tadic, 1994;Phillips, 1999;Abdel-Wahhab et al, 1999;Hassen et al, 2003;Katsumata et al, 2003;Dominy et al, 2004). Bartko et al (1983) and Boranic (2000) emphasized the high selective ion exchange capacity of clay minerals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They can firmly and selectively bind harmful substances from feeds in the intestines and thus reduce their absorption across the intestinal mucosa and resulting toxic effect (Knezevic and Tadic, 1994;Phillips, 1999;Abdel-Wahhab et al, 1999;Hassen et al, 2003;Katsumata et al, 2003;Dominy et al, 2004). Bartko et al (1983) and Boranic (2000) emphasized the high selective ion exchange capacity of clay minerals.…”
Section: Discussionmentioning
confidence: 99%
“…When kaolin is added to animal diets, it reduces resorption of harmful toxins present in the feed through intestinal mucosa to the organism because it binds them firmly and selectively, and thus eliminates their toxic effects. A number of studies have demonstrated the excellent ability of kaolin to decontaminate enterotoxins which cause diarrhoea (Dominy et al, 2004), aflatoxins (Schell et al, 1993;Abdel-Wahhab et al, 1999;Phillips, 1999), plant metabolites (alkaloids, tannins), pathogenic microorganisms, heavy metals (Hassen et al, 2003;Katsumata et al, 2003), and poisons (Knezevich and Tadic, 1994). Kaolin added to farm animal diets can also influence their efficiency and perhaps also quality of meat (Savory 1984;Sakata, 1986;Kolacz et al, 2005).…”
mentioning
confidence: 99%
“…(Gebesh et al, 1999;Heimann, 1984;Kasi et al, 1995;Trckova et al, 2004). 많은 연구결과에서도 고령토는 체내에서 아플라톡신(aflatoxin; Abdel-Wahhab et al, 1999;Phillips, 1999)을 배출하고 장독소(enterotoxins; Dominy et al, 2004), 병원성 미생물 (Hassen et al, 2003), 중금속 (Katsumata et al, 2003) 및 독소(poison; Knezevich and Tadic, 1994)로 인한 설사를 방지하는 능력이 있는 것으로 나타났다. 실제로, 육계사료 에 2.5~8%의 고령토를 첨가하면 에너지 이용효율이 개선되며 (Ousterhout, 1967) 병아리에게 6%의 kaolin 사료를 급여하면 약 6%의 사료효율 개선효과가 있다는 보고도 있다 .…”
Section: 서 론unclassified
“…Hassen and his coworkers found that the tested clay substrate appeared as a relatively moderate phage adsorbent since the quantity of adsorbed phage averaged 98.2 AE 0.88%. He also reported that the retention capacity of purified clay Kbl2 appeared to be 60% for Pseudomonas aeruginosa (Hassen et al, 2003).…”
Section: Ammonia and Nitrogen Dioxide Emissionsmentioning
confidence: 99%